2022
DOI: 10.2147/ppa.s337448
|View full text |Cite
|
Sign up to set email alerts
|

Poor Compliance Causes Acute Rejection in Kidney Transplant Recipients During COVID-19 Pandemic: 2 Cases Report

Abstract: The COVID-19 pandemic has lasted for more than one year, which caused much trouble to the health management of kidney transplant recipients. Numerous patients cancelled their review appointment or even lost connection with doctors because of the great pressure medical system undergoing, strict travel restrictions, and the worries about COVID-19 infection risk. Herein, we introduce two kidney transplant recipients, a 33-year-old man and a 32-year-old man, who did not take the immunosuppressant drugs and did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…After the exclusion of duplicates and articles that did not fulfill the study inclusion criteria, fifty-two articles were included in the qualitative synthesis of this systematic review. The reports of ninety-six cases (fiftysix organ rejection cases following COVID-19 vaccination [7][8][9][10][11] and forty organ rejection cases after COVID-19 infection [12][13][14][15][16][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]) identified from these articles are presented in groups based on confirmed diagnoses, laboratory, biopsy and imaging findings. The detailed characteristics of the included studies are shown in Tables 1 and 2.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…After the exclusion of duplicates and articles that did not fulfill the study inclusion criteria, fifty-two articles were included in the qualitative synthesis of this systematic review. The reports of ninety-six cases (fiftysix organ rejection cases following COVID-19 vaccination [7][8][9][10][11] and forty organ rejection cases after COVID-19 infection [12][13][14][15][16][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]) identified from these articles are presented in groups based on confirmed diagnoses, laboratory, biopsy and imaging findings. The detailed characteristics of the included studies are shown in Tables 1 and 2.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Cells in the anterior chamber There were 42 case reports [5][6][7][8][11][12][13]17,18,[20][21][22][24][25][26][27][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][48][49][50][51][52][53][54][55][56][57], 8 case series [9,10,14,28,36,46,47,58] and 2 cohort studies [19,23]. These studies were conducted in t...…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 3 more Smart Citations